Organic Optoelectronic Materials - Li, Yongfang (Lecture Notes in Chemistry, 2015)
This volume reviews the latest trends in organic optoelectronic materials. Each comprehensive chapter allows graduate students and newcomers to the field to grasp the basics, whilst also ensuring that they have the most up-to-date overview of the latest research. Topics include: organic conductors and semiconductors; conducting polymers and conjugated polymer semiconductors, as well as their applications in organic field-effect-transistors; organic light-emitting diodes; and organic photovoltaics and transparent conducting electrodes. The molecular structures, synthesis methods, physicochemical and optoelectronic properties of the organic optoelectronic materials are also introduced and described in detail. The authors also elucidate the structures and working mechanisms of organic optoelectronic devices and outline fundamental scientific problems and future research directions. This volume is invaluable to all those interested in organic optoelectronic materials.